THE INFLUENCES OF PROMOTION, PERCEIVED EASE OF USE AND PRICE TO PURCHASE INTENTION OF INDRIVE IN MANADO - Hizkia Marsud; Frederik G. Worang; Emilia M. Gunawan (Universitas Sam Ratulangi, 2024)
This study aims to analyze the influence of Promotion, Perceived Ease of Use and Price to Purchase Intention. The researcher used InDrive users in Manado as object. Quantitative research is used for testing objective theories by examining the relationship of variables. The number of samples used in this study is 100 respondents, aged 18-26, sampling method that was used is random sampling, with questionnaire as a tool in collecting data. Multiple regression analysis is used to analyze the relationship between dependent variable and two or more independent variable. The result shows that Promotion have no influence on Purchase Intention, Perceived Ease of Use have no influence on Purchase Intention, Price has a positive and significant effect on Purchase Intention and Promotion, Perceived Ease of Use and Price simultaneously have a significant effect on Purchase Intention. Keywords: Promotion, Perceived Ease of use, Price, Purchase Intention